History of Ancient Greek Scholarship : From the Beginnings to the End of the Byzantine Age - Montanari, Franco, (Classical Studies E-Books Online, Collection 2020, ISBN: 9789004393820., 2020)
This book aims to offer a unified historical treatment of all that is usually understood as "ancient scholarship" or "ancient philology" and is the first modern work to cover a period from the beginnings to the fall of Byzantium after John Edwin Sandys' work published between 1903-1908. The field "ancient scholarship" includes the exegesis of Greek authors, the editing of their texts, orderly collections of materials useful for exegetical purposes - such as lexeis , onomatologies, collections of antiquarian materials et similia -, the study of grammar, reflection on language, and everything that can be linked to this sphere, that is to say literature and the instruments for interpreting it. If it is hard today to imagine such a work being undertaken by a single scholar, it is worth underlining the benefits offered by a volume with multiple expert voices in a field so complex and multiform. The book is based on the four historiographical chapters of Brill's Companion to Ancient Greek Scholarship (2015), which have been enlarged, updated and rethought.